A Pilot Study Exploring Caregivers' Experiences Related to the Use of a Smart Toothbrush by Children with Autism Spectrum Disorder - Katherine France; Olivia Urquhart; Eugene Ko; Juliana Gomez; Maria Ryan; Matilde Hernandez; Marta Gabinskiy; Patricia M. Corby; Mark S. Wolff (MDPI AG, 2024)
Background: Research on caregivers for children with intellectual disabilities, particularly those with autism spectrum disorder (ASD), has highlighted several obstacles to achieving better oral health. These include challenges with tolerating oral care, sensory processing differences, uncooperative behaviors, and communication impairments. There is limited understanding of what caregivers would consider "successful assistance" in improving oral health for these children. Objectives: This pilot study aimed to examine caregivers' and user's experiences with a Kids Smart Electric Toothbrush used by children with ASD. Methods: It involved open-ended interviews and questionnaires with caregivers prior to utilization of the toothbrush and after 4 weeks of product use by the child. Results: Seventeen children with ASD, aged 5-12, participated. A total of 58.8% of caregivers said their child brushed more often, and all reported brushing at least twice a day by week 4. Caregivers reported that children became more independent while brushing their teeth and achieved better quality brushing. Caregivers' frustration with the brushing process, satisfaction with the device, and need to assist the child with brushing were improved. Caregivers did encounter some technical difficulties with the app. Conclusion: This study will assist in exploring "smart" toothbrush technologies for oral hygiene in children with ASD.